Small nucleolar RNA host gene 1 promotes development and progression of colorectal cancer through negative regulation of miR‐137. Issue 11 (30th August 2019) - Fu, Yang; Yin, Yuhan; Peng, Sanfei; Yang, Ge; Yu, Yang; Guo, Changqing; Qin, Yanru; Zhang, Xiefu; Xu, Wen; Qin, Yiyu
Abstract: Small nucleolar RNA host gene 1 (SNHG1) is critical in the progression of cancers. However, the mechanism by which SNHG1 regulates the progression of colorectal cancer (CRC) remains unclear. Expressions of SNHG1 and miR‐137 in CRC tissues and cell lines were evaluated by quantitative real‐time polymerase chain reaction. A luciferase reporter gene assay was conducted to investigate miR‐137 target. Additionally, RNA pull‐down assay was performed to explore the physical association between miR‐137, SNHG1, and RNA induced silencing complex (RISC). Cell cycling and invasion were examined by flow cytometry (FCM) and transwell assays. The in vivo carcinogenic activity of SNHG1 was examined using murine xenograft models. Expression of RICTOR, serine/threonine kinase 1 (AKT), serum and glucocorticoid‐inducible kinase 1 (SGK1), p70S6K1, and LC3II/LC3I ratio was examined by Western blot analysis. SNHG1 upregulation was observed in CRC tissues and cell lines, which was associated with the lymph node metastasis, advanced TNM stage and poorer prognosis. SNHG1 increased RICTOR level in CRC via sponging miR‐137. In addition, SNHG1 silencing inhibited CRC cell proliferation and migration in vitro and in vivo. SNHG1 regulated RICTOR expression by sponging miR‐137 and promoted tumorgenesis in CRC.